Penerapan Kaidah Fiqh dalam Hukum Media Sosial di Era Globalisasi Ilmu Pengetahuan dan Teknologi - Sakka, Syamsuddin; Al-Kautsar, Muhammad Syakir (Palita: Journal of Social Religion Research, 2024)
The globalization of science and technology continues, especially on social media. On the one hand, the benefits of various conveniences are also clearly felt to cause harm. The research examines social media laws and the limitations of their use concerning fiqh rules. This research includes normative legal research methods with a conceptual approach in the form of Islamic law principles. The study concludes that the original law of social media is permissible (permissible) and will change to be recommended if it brings benefits and change to be forbidden if it causes damage. However, the potential for harm in social media exists, so there must be limits to its use and regulatory restrictions, especially restrictions that apply widely in society through state policymaking. The research results can be considered when responding to developments in technology and information, especially regarding social media, so that we can use social media more wisely. Keywords: Social Media Law, Fiqh Rules, Era of Globalization of Science and Technology